Techno-economical analysis of hybrid PV system for school industry - Akbar, Muhammad Rezeki; Aripriharta; Mizar, Alfian; Muladi, Muladi; Ching, Hung-Yu; Amin, Muhammad Adib (2023)
Electrical energy is currently one of the most important needs of the community and as the most important economic resource needed in various activities. The need for electrical energy every year continues to increase. However, the rapid development of electricity consumption is not matched by the growth of power generation. To overcome these problems, alternative energy sources are needed as a substitute for coal. One of the renewable natural resources is solar energy. To harvest this energy, a device called a solar panel or photovoltaic is needed. This study discusses the design of solar power plant in PPPI Al-Ittihad using technical and economic analysis. This solar power generation system is designed to supply electricity needs to help with daily activities. The design of this solar power plant requires 10 solar modules with a capacity of 120 wp, 1 inverter with a capacity of 5 kW, and 4 units of 12 V/200 Ah batteries. The initial investment cost for this solar power generation system is Rp22,398,435. Analysis of the feasibility of investing in a solar power plant system shows a positive Net Present Value (NPV) value of Rp32,208,93095, Internal Rate of Return (IRR) 10.0171% and Profitability Index (PI) 1.001437999. The NPV, IRR, and PI values show positive values, so the investment for this solar power generation system project can be said to be feasible. As for the payback period, it is achieved in the 9th year of the project's operating period.